Measure the Fear of Anxiety of Future Among the Students of Zakho University and Their Peers from Mosul University Students - Abdulahad, khlood B. (Humanities Journal of University of Zakho, 2017)
The study aimed to measure the fear of anxiety of future concern among the students of Zakho University and their peers from Mosul University students (displaced students) through the identification of: - concern for the future of the zakho university students. future concern of Mosul University Students (displaced to Dohuk governorate) alternate location Are there significant statistical differences about future concern in accordance with the following variables university (Zakho University students and their displaced peers from Mosul University) students. Gender (males - females). department (scientific - humanities). Community of the research (1602) students in Zakho University has included (936 male) and (666 female) students from scientific and humanitarian departments, and (866) students from the University of Mosul (alternate location) by (602) male and (264) female students from both scientific and humanitarian major, the research sample was choose randomly and by 120 students from the scientific departments of Zakho University and the same of the University of Mosul and the total sample reached (240) students, the study used a(prepared scale) to achieve the objectives of the research, a scale of concern to the future prepared by Khalidi (2002) has been extracted sincerity and persistence to make sure of the validity then has been applied to the final measure of the research sample the average time it takes to respond was(35) minutes, and treated with the data obtained statistically using T-test for one sample and two in depended samples and Pearson correlation coefficient the study found the following results: that the students of the University of Zakho do not sense of anxiety about the future. Mosul University students have suffered from future anxiety concern. males are more anxiety about the future than the female. There are differences in the future anxiety , according to the variable of specialization (science – human). The research found a set of recommendations and proposals, including: paying attention to guidance and psychological counseling at universities, especially for Mosul University students. speed up the process of finding solutions and achieving security and the return of displaced people to their home areas. The main proposals are: Applying a similar study to see concern the future of the displaced students and their peers from other universities. make a comparative study of the variable future concern with other variables academic stage